2004
DOI: 10.1002/jez.a.130
|View full text |Cite
|
Sign up to set email alerts
|

Sodium or potassium ions activate different kinetics of gill Na, K-ATPase in three seawater- and freshwater-acclimated euryhaline teleosts

Abstract: The effects of [Na(+)] or [K(+)] on Na, K-ATPase activity of FW-acclimated and SW-acclimated tilapia, puffer and milkfish were examined in gill homogenates. [Na(+)] or [K(+)] stimulated Na, K-ATPase hydrolyzing ATP in all experimental groups. ATP hydrolysis stimulated by [Na(+)] or [K(+)] followed Michaelian-Menten kinetics. Km values for [K(+)] (i.e., Km(K)), were lower in SW- than FW-acclimated tilapia and puffer fishes (tilapia: 8.69+/-0.22 vs. 11.93+/-1.17 mM; puffer: 13.51+/-1.39 vs. 30.52+/-2.66 mM). Km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 43 publications
(21 reference statements)
1
11
1
Order By: Relevance
“…Similar results have been reported in other euryhaline teleosts such as A. s. schlegelii (Kelly et al, 1999), R. sarba (Deane & Woo, 2004), Morone saxatilis (Walbaum 1792) (Tipsmark et al, 2004) and Sparus aurata L. 1758 (Laiz-Carriòn et al, 2005), where the activity and expression of naka were lower at intermediate salinities (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). These results seem to contradict those reported by Hwang & Lee (2007), Lin & Lee (2005) and Lin et al (2004) in Mozambique tilapia Oreochromis mossambicus (peters 1852), where there were higher naka expression levels in sea-water than in fresh water, but salinities approaching iso-osmotic conditions were not tested, so a potential U-shaped expression pattern could not be revealed.…”
Section: N T E R P R E Tat I O N O F T H E D I S T I N C T C O -E Xcontrasting
confidence: 88%
“…Similar results have been reported in other euryhaline teleosts such as A. s. schlegelii (Kelly et al, 1999), R. sarba (Deane & Woo, 2004), Morone saxatilis (Walbaum 1792) (Tipsmark et al, 2004) and Sparus aurata L. 1758 (Laiz-Carriòn et al, 2005), where the activity and expression of naka were lower at intermediate salinities (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). These results seem to contradict those reported by Hwang & Lee (2007), Lin & Lee (2005) and Lin et al (2004) in Mozambique tilapia Oreochromis mossambicus (peters 1852), where there were higher naka expression levels in sea-water than in fresh water, but salinities approaching iso-osmotic conditions were not tested, so a potential U-shaped expression pattern could not be revealed.…”
Section: N T E R P R E Tat I O N O F T H E D I S T I N C T C O -E Xcontrasting
confidence: 88%
“…It was suggested that a1-and a3-like proteins might play the role for osmo-or ionoregulation but a2-like protein probably performed the other physiological function. The affinity of gill NKA for sodium increased significantly in warm-acclimated Antarctic teleost (T. bernacchii; Morrison et al, 2006) that is opposite to milkfish, which has lower sodium affinity in SW than FW (Lin and Lee, 2005). Upregulation of gill a1-and a2-like proteins influenced sodium affinities and fulfilled some of the requirements for the subtly moderated enzyme behaviors (e.g., elevated NKA activity) in warmacclimated T. bernacchii (Morrison et al, 2006), while the changes in gill NKA a1-and a3-like proteins may play the potential role for reduction of sodium affinities to decrease NKA activity in SW-exposed milkfish.…”
Section: Discussionmentioning
confidence: 97%
“…M, marker; SW, seawater; HSW, hypersaline water. SW-acclimated milkfish (Lin and Lee, 2005). Therefore, alteration of NKA activity in gills of fish following salinity changes may result from different NKA isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some studies demonstrated different substrate affinities for gill NKAs between SWand FW-acclimated tilapia (28) and rainbow trout (O. mykiss) (33), and both tilapia and rainbow trout were found to express NKAs with different combinations of ␣-subunits, depending on environmental salinities (14,23,37). On the other hand, the different responses to endocrine or environmental factors among NKA ␣-isoforms (or ␣1 paralogues) should also be considered when discussing the physiological significances of the existence of multi-isoforms of NKA ␣-subunits.…”
Section: Discussionmentioning
confidence: 98%